(untitled) (AYUSHDHARA, 2024)
Yoga is an ancient way of living that provides physical, mental, emotional and spiritual health. Yoga cures many chronic diseases and bring a state of relaxation for overall well-being. In today’s scenario diseases start due to a sedentary lifestyle, wrong behavior, negative thoughts and attitudes. All this creates an imbalance in the human body, according to Ayurveda these habits vitiate Tridosha that is Vata, Pitta and Kapha. These three humor of human existence governs bodily function. In Ayurvedic classical text, all the skin diseases have described under the common heading ‘Kushtha’. Kitibha is one of the types of Kushtha and considered under category of Kshudra Kushtha is correlated with Psoriasis due to close resemblance of their clinical features. The mental and physical pain involved in the psoriasis affect the health of patients. The Ayurveda text elaborates the symptoms, causes and diagnosis of vitiated Dosha while the Yoga text explains the techniques which purify Dosha from the body and provide balance among three Vata, Pitta and Kapha. These three Dosha are essential constitutions of the living being. A balanced functioning of these three Dosha in living being considered a healthy individual and disharmony of these three Dosha could lead to many chronic illnesses. According to Ayurveda, no disease manifests without the Vaisamya of Dosha. Yoga provides a holistic approach to managing skin conditions.